Exoscope as a Teaching Tool: A Narrative Review of the Literature - Calloni, Tommaso; Roumy, Louis Georges; Cinalli, Maria Allegra; Rocca, Alessandra; Held, Andrea; Trezza, Andrea; Carrabba, Giorgio Giovanni; Giussani, Carlo Giorgio (Frontiers in Surgery, 2022)
Recently, the emergence of the three-dimensional (3D) exoscope has proven to be a viable alternative to the operative microscope (OM) as a novel work horse of microneurosurgical procedures. Through its current iteration, the 3D exoscope has been demonstrated to be at least equivalent to the operative microscope in terms of surgical outcome in many settings. With its superior ergonomics and simplicity of use, the 3D exoscope has been shown in multiple studies to be a powerful visualizing tool during surgical procedures. Moreover, the exoscopic systems, through their current iterations, by means of a high-resolution 3D monitor and 3D glasses, have allowed all participants present on the operative room to attain an unprecedented level of intraoperative visualization of anatomical structures and surgical maneuvers, traditionally only available to the first operator. Although long-term data is still lacking regarding its future as a replacement of the OM, the 3D exoscope has revealed itself as an intense subject of discussion in neurosurgery regarding its implication for surgical education, especially for residents and junior neurosurgeons. The present paper is a review on the current state of the literature on role of the exoscope in surgical education, underlining its strength as a learning tool and its potential future implications in terms of surgical education.